The firm : the inside story of the Stasi - Bruce, Gary 1969- (The Oxford oral history series, 2010)
"The Stasi, East Germany's secret police was the largest per capita secret police in world history. The territorial units of the Stasi, the small offices that dotted the countryside and undertook the lion's share of internal surveillance, responsible for running the majority of the Stasi's Informants or societal "collaborators," have received virtually no attention in the scholarly literature. The Firm will be the first book to trace the history of the Stasi at a district level. Based on previously inaccessible secret police files and interviews with former members of the East German security apparatus, it provides an unparalleled picture of life in a totalitarian state. This book is based on 14 interviews with former secret police personnel from the districts under study, the most interviews ever conducted with former Stasi by one person, and 30 interviews with "ordinary" people in the districts in order to address daily life in a dictatorship, as well as the regional Stasi archives. This book will it provide a new approach to understanding totalitarianism and life in a late 20th century police state and will address major issues such as the use of intelligence in the concept of security and the limits of an "acceptable" level of surveillance"--